In his own words from freedom to the future : tributes and speeches - Mandela, Nelson 1918-2013 (Abacus, 2004)
IN HIS OWN WORDS is a selection of Nelson Mandela's speeches, providing a lively, memorable profile of his lifelong commitment to freedom and reconciliation, democracy, and the flourishing of all the people of South Africa, Africa and the world. Arranged thematically, each section of speeches is introduced by a leading figure, such as Kofi Annan and Desmond Tutu. In these introductory essays, the authors pay tribute to Nelson Mandela's achievements, animating their accounts with personal memories, stories and reflections. Covering a range of topics of our times - struggle and reconciliation, freedom, religion and nation building, culture, education and health, children and development - the book also features Mandela's own tributes to South African heroes such as Steve Biko, Oliver Tambo and Walter Sisulu.